Is Spain really different?. A comparative analysis of court fess and civil and commercial mediation in Spanish and English law - Liébana Ortiz, Juan Ramón (REVISTA GENERAL DE DERECHO PUBLICO COMPARADO, 2018)
This paper carries out a comparative study of the Court fees and the Civil and Commercial mediation both in Spanish Law and English Law, in order to extract their main similarities and differences and to analyse the impact that Court fees have in the effective access to Justice for citizens and companies alike, as well as the correlative enhancement of mediation as an alternative dispute resolution system in the Spanish and British legal systems.
Keywords: court fees; civil & commercial mediation; Spanish Law; English Law; Emerging